The romance of race : incest, miscegenation, and multiculturalism in the United States, 1880-1930 - Sheffer, Jolie A. (Rutgers University Press, 2012)
The national identity of the United States was transformed between 1880 and 1930 due to mass immigration, imperial expansion, the rise of Jim Crow, and the beginning of the suffrage movement. This book examines the role of minority women writers and reformers in the creation of modern American multiculturalism by placing minorities at the center of American identity and imagining a new national narrative based on the model of an interracial nuclear family.